PENGARUH PENGELUARAN PEMERINTAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO PADA KORIDOR UTARA SELATAN DI PROVINSI JAWA TIMUR - M Amirul Muminin; Wahyu Hidayat Riyanto (Jurnal Ilmu Ekonomi JIE, 2017)
This study aims to determine the effect of Economic Growth and Population on Open Unemployment Rate in East Java Province in 2011-2015. Data Analysis Tool used in this study was Panel Data Regression. The findings showed: 1) Economic Growth had a significant negative effect on Open Unemployment Rate, which is if Economic Growth rises by 1%, the Open Unemployment Rate decreases by -0.282, 2) Population positively and significantly influence the Open Unemployment Rate, which is indicated that every increase of 1% of the population, the Open Unemployment Rate would also rise by 0.001. The Coefficient of Determinant (R2) was 0.967435 or 96.7453%. This shows the ability of independent variables, (Economic Growth (X1) and Total Population (X2) in explaining dependent variable (Open Unemployment Rate (Y)) equal to 0.967435 or 96.7453% while the rest 3.2565% explained by other variable outside the model.Keywords: open unemployment rate, economic growth, population number